Technique of analyzing device drivers of embedded linux system using UML - Liang MA; Li LI; Su-bin SHEN (Tongxin xuebao)
A method to model and analyze the device drivers in embedded Linux system using UML was proposed.By using UML modeling method,the dependencies among the device driver components and the focus of the device driver development are clarified.On this basis,the SDWiFi device driver model was studied,the SDIO communication interface between the host and Wi-Fi chips was designed and the SDWiFi device driver was transplanted.At last,the SDWiFi wireless LAN equipment was configured and tested using wireless tools.The test results show that the SDWiFi wireless LAN equipment works properly.The efficiency of the device driver development is improved by modeling and analyzing the device drivers using UML.